Analysis of Risk Factor Traffic Crashes and Implementation of Road Safety: A Systematic Literature Review - ST, adenan; Lubis, Siti Rahmah Hidayatullah; Mardiana, Dewi (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Every year, RTA (Road Traffic Accident) kills roughly 1.19 million people globally and injures between 20 and 50 million people. The projected financial impact of these accidents is 518 billion per year, and numerous households suffer lifetime physical disability and mental trauma as a result of these fatal road accidents. This study aims to assess risk factors for traffic crashes and the implementation of road safety. Method: This research technique is a systematic literature review that examines 27 journal articles published between 2020 and 2024. The author used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020. Results: Most countries have established comparable policies, such as punishing illegal activity, regulating speed, increasing driving, helmet use, drinking and driving, and road safety education. The issues that remain include unsafe behavior still being violated by the community and a lack of awareness about the need for road safety implementation Conclusion: The government must consider acceptable tactics for educating people about the necessity of following traffic regulations, improving current policies, and utilizing technology to help prevent traffic accidents. Pendahuluan: Setiap tahun, RTA (Kecelakaan Lalu Lintas Jalan) menewaskan sekitar 1,19 juta orang di seluruh dunia dan melukai antara 20 dan 50 juta orang. Dampak finansial yang diproyeksikan dari kecelakaan ini adalah 518 miliar per tahun, dan banyak rumah tangga menderita cacat fisik dan trauma mental seumur hidup sebagai akibat dari kecelakaan jalan yang fatal ini. Studi ini bertujuan untuk menilai faktor risiko kecelakaan lalu lintas dan penerapan keselamatan jalan. Metode: Teknik penelitian ini adalah tinjauan pustaka sistematis yang meneliti 27 artikel jurnal yang diterbitkan antara tahun 2020 dan 2024. Penulis menggunakan Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020. Hasil: Sebagian besar negara telah menetapkan kebijakan yang sebanding, seperti menghukum aktivitas ilegal, mengatur kecepatan, meningkatkan mengemudi, penggunaan helm, minum dan mengemudi, dan pendidikan keselamatan jalan. Permasalahan yang masih terjadi antara lain masih banyaknya perilaku tidak aman yang dilanggar oleh masyarakat serta kurangnya kesadaran terhadap perlunya penerapan keselamatan jalan. Kesimpulan: Pemerintah harus mempertimbangkan taktik yang dapat diterima untuk mendidik masyarakat tentang pentingnya mematuhi peraturan lalu lintas, meningkatkan kebijakan saat ini, dan memanfaatkan teknologi untuk membantu mencegah kecelakaan lalu lintas.